Aging and economic growth: empirical analysis using autoregressive distributed lag approach - Ismail, Normaz Wana; Haji Abd Rahman, Hajah Siti Wardah; Tengku Abdul Hamid, Tengku Aizan; Said, Rusmawati (Universiti Kebangsaan Malaysia, 2016)
The purpose of this study was to examine the impact of aging on economic growth.The study used dynamic growth model and employed Autoregressive Distributed Lag (ARDL) approach for the period of 1980 to 2011. Three proxies for aging are used namely fertility rate, life expectancy and old dependency ratio. However, only fertility rate is detected to have a long run cointegration. The major finding of this study showed that a reduction of fertility rate lead to higher economic growth. This implied that even though Malaysia will face aging society by 2020, the economic growth is still stable and can increase by investing more on human capital.